Cyber Physical System – Smart Cloud Traffic Control - Hahanov, V. I.; Wajeb Gharibi; Abramova, L. S.; Chumachenko, S. V.; Litvinova, E. I.; Hahanova, A. V.; Rustinov, V.; Miz, V.; Zhalilo, A.; Ziarmand, A. (EWDTS, 2014)
A cyber physical system for smart cloud traffic control is proposed. It is an intellectual (smart) road infrastructure for monitoring and control of traffic in real-time through the use of global systems for positioning and navigation, mobile gadgets and the Internet in order to improve the quality and safety of vehicle movement, as well as for minimizing the time and costs when vehicles are moved at the specified routes. The main innovative idea is step-by-step transfer of traffic lights from the ground to a virtual cloud space for vehicle management, equipped with a mobile gadget or computer, which displays on the screen map, route, coordinates of the road user and real traffic signals. A set of innovative technologies to address the social, humanitarian, economic, energy, insurance, crime and environmental problems through the creation and application of cloud-based digital traffic monitoring and management is developed. All of these technologies and functional components are integrated into the system automaton model of cyber physical system for interaction between an infrastructure cloud of exact monitoring and digital control and vehicle gadget or computer.
Keywords: cyber physical system; smart cloud traffic control